On the Progress of the Information Service System LASSIE - AOKI, Shizue; KAWASHIMA, Hajime (Igaku Toshokan, 1992)
We have devised a science information retrieval system which we call LASSIE (Lan-Associated Service System for Informational Exploration). This system enabled scientists of the Showa Campus of Gunma University to retrieve CD-ROM MEDLINE or CCoD from their own laboratories. One year has passed since the LASSIE system entered service via the Showa Campus LAN, and the service records throughout this period are presented. Meanwhile, the GUNet (Gunma University Integrated Academic Information Network System) was constructed by the Computer Center of the University. This network connects the university's three campus LANs by super digital line. By connection with the GUNet, the LASSIE system was expanded to all the campuses of the University. Through the new LASSIE system we can provide access to the CD-Servers at the Showa and Aramaki campuses, which are connected to a NetWare network system by a IPX protocol, and to OPAC (Online Public Access Catalog) in the Computer Center and NACSIS-IR by a TCP/IP protocol. The detailed records of advances in the system are also presented.